2019
DOI: 10.1002/pros.23928
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator‐activated receptor gamma controls prostate cancer cell growth through AR‐dependent and independent mechanisms

Abstract: BackgroundProstate cancer (PC) remains a leading cause of cancer mortality and the most successful chemopreventative and treatment strategies for PC come from targeting the androgen receptor (AR). Although AR plays a key role, it is likely that other molecular pathways also contribute to PC, making it essential to identify and develop drugs against novel targets. Recent studies have identified peroxisome proliferator‐activated receptor gamma (PPARγ), a nuclear receptor that regulates fatty acid (FA) metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…Studies have been conducted with more-specific inhibitors that strengthen FAS as an anticancer target. Fasnall was shown to inhibit breast cancer 245 and prostate cancer cell growth 262 , and GSK2194069 inhibits the proliferation of non-small-cell lung cancer cell lines 248 . IPI-9119 (reF.…”
Section: Nafld-nash and Type 2 Diabetesmentioning
confidence: 99%
“…Studies have been conducted with more-specific inhibitors that strengthen FAS as an anticancer target. Fasnall was shown to inhibit breast cancer 245 and prostate cancer cell growth 262 , and GSK2194069 inhibits the proliferation of non-small-cell lung cancer cell lines 248 . IPI-9119 (reF.…”
Section: Nafld-nash and Type 2 Diabetesmentioning
confidence: 99%
“…Small molecular inhibitors however may have even fewer side effects. Use of one small molecule, T0070907, was shown to impair growth of PC cell lines LCP and PC3 in vitro [70]. LCP cells were also used in a xenograft and treated with T0070907 whereupon 4/7 tumours could no longer be detected indicating a complete regression.…”
Section: %mentioning
confidence: 99%
“…Interestingly, regarding factors involved in cell cycle, another study has found that the pro-apoptotic genes c-Myc and Bax are inhibited while cell-cycle regulators PCNA, cyclin D1 and COX-2 are promoted along with PPAR-g activation (40,55). In several studies, with the cell culture of human renal cell carcinoma, human prostate cancer xenografts in nude mice, as well as brain cancer in vivo, the increased expression of PPAR-g are all prognostically negative and pro-metastatic (56)(57)(58).…”
Section: Promotion Of Tumorigenesismentioning
confidence: 99%